EKSISTENSI HAK ATAS TANAH DAN PENGADAAN TANAH UNTUK KEPENTINGAN UMUM - Rahmatullah Rahmatullah; Rizka Amelia Armin; Nurul Adliyah (Al-Amwal : Journal of Islamic Economic Law, 2022)
The state of Indonesia is a legal state; this provision is guaranteed in the 1945 Constitution of the Republic of Indonesia (1945 Constitution of the Republic of Indonesia). The legal state of Indonesia is based on the concept of a welfare state, which aims for the greatest prosperity of the people. One of the most important natural resources for ensuring prosperity in the Indonesian legal state in the current era of globalization is land. The urgency of land for human life was appreciated by the government of the Republic of Indonesia through the national land policy with the issuance of Law Number 5 of 1960 concerning Agrarian Principles. Land acquisition is a government activity that involves acquiring land for various developments, especially those of public interest. Land acquisition for public purposes refers to Article 6 of the UUPA, which states that all land rights have a social function. The development of the public interest is regulated in Law No. 12/2012 concerning Land Acquisition for Development in the Public Interest. The implementing regulations have regulated the mechanism of land acquisition by the government for public development as well as the rights and legal remedies available to land owners.